Integrated weed management with reduced herbicides in a no‐till dairy rotation. (8th July 2021) - Summers, Haleigh; Karsten, Heather D.; Curran, William; Malcolm, Glenna M.
Abstract: With more than 65% of agronomic crops under no‐till in Pennsylvania, herbicides are relied on for weed management. To lessen the environmental impact and selection pressure for herbicide resistance, we conducted a 9‐yr experiment to test herbicide reduction practices in a dairy crop rotation at Rock Springs, PA. The rotation included soybean [ Glycine max (L.) Merr.]–corn ( Zea mays L.)–3‐yr alfalfa ( Medicago sativa L.)–canola ( Brassica napus L.). The following practices were used to reduce herbicide inputs: (a) banding residual herbicides over corn and soybean rows and using high‐residue inter‐row cultivation; (b) seeding a small grain companion crop with alfalfa; (c) plowing once in 6 yr to terminate the perennial forage. These practices were compared with standard herbicide‐based weed management (SH) in continuous no‐till. We hypothesized: (a) There would be more weed biomass in the reduced herbicide treatment (RH), (b) leading to more weeds in RH over time, but (c) the added weed pressure would not affect yield (d) or differences in net return. We sampled weed biomass in soybean, corn, and the first two forage years. In corn and soybean, weed biomass was often greater in RH than SH and increased over the years in the RH treatments. In the forage, weed biomass did not always differ between treatments. Yield and differences in net return were similar in most crops and years. Results suggest that weed management with reduced herbicide inputs supplemented with an integrated approach can be effective but may lead to more weeds over time. Core Ideas: Weed control with banded herbicide and cultivation was less effective than broadcast herbicides. With banded herbicide plus cultivation, weed biomass increased in row crops across years. Even with more weeds, crop yield and net difference in returns were similar between systems. In the perennial forage, weed biomass and crop yield were similar between systems. Weeds were consistently low in the 2nd‐year forage regardless of management.